ILRI medium-term plan 2001-2003. Making the livestock revolution work for the poor - International Livestock Research Institute (International Livestock Research Institute, 2000)
ILRI's medium-term plan (2001-2003) addresses the recommendations of ILRI's first EPMR and follows the directions and priorities set out in the Board approved ILRI strategy to 2010. This document highlights characteristics of ILRI's MTP for 2001-2003, and describes ILRI's strategic choices, priority setting, monitoring and evaluation, core capacities, production-to-consumption systems project, strategy for the CGIAR in sub-Saharan Africa and presents summary of 1999 results and 2000 Developments. It also outlines highlights of changes for 2001, major features of the 2002-2003 project portfolio, changes in milestones, collaboration highlights, centre staffing highlights, project cost components, centre financial health indicators, and financial planning. The three annexes at the end of the document presents project portfolio 2001-2003 (project descriptions and logical frameworks); a frame work for assessing priorities; and ILRI partners. Efficient and economical methods of seed harvesting are required for use by small-scale forage seed producers in developing countries. Three common, simple methods (hand picking as seed ripens, beating ripe seed from standing plants, and cutting the entire plot when seed is at maximum ripeness) were studied using three common small-seeded forages (Stylosanthes guianensis, S. scabra, and Desmodium intortum). Yield of mature seed, labor, and time were compared. For both Stylosanthes spp., maximum seed yield from minimum labor input were obtained by cutting the plot at maximum ripeness and threshing out the mature seed. The highest seed yield from D. intortum was achieved by using a combination of picking and cutting. However, this required more labor than cutting the entire plot at peak maturity.